Shared decision-making within goal-setting in rehabilitation: a mixed-methods study. (March 2019) - Rose, Alice; Soundy, Andy; Rosewilliam, Sheeba
Objectives: To assess the extent of shared decision-making within goal-setting meetings and explore patient-reported factors that influenced their participation to shared decision-making about their goals. Design: A two-phase explanatory sequential mixed-methods study, using questionnaires and interviews. Setting: A rehabilitation centre and patients' homes. Subjects: Frail elderly patients. Main Measures: Quantitative data were collected after every patient's goal-setting meeting using the Multifocal Approach to Sharing in Shared Decision Making (MAPPIN'SDM) questionnaire that assesses competencies relevant to shared decision-making. Shared decision-making was rated by an observer, patients and staff and compared. Qualitative data were collected through semi-structured interviews. Results: A total of 24 rehabilitation team members and 40 patients (mean age: 83 years) participated. All study participants felt that competency 7a (the language used by staff made sense to the patient) was observed in all meetings. Patients reported that for 22 of the meetings competency 4a, the advantages and disadvantages of rehabilitation, was not discussed. Games-Howell tests for direction of differences between groups showed significant difference ( P = 0.001) between patients and staff in whether patients' problems were discussed. Nine patients' interviews suggested that motivation, self-confidence, family support, preparing themselves, getting information about goal-setting and rehabilitation options could enable them to participate in shared decision-making. They suggested that staff should communicate clearly and demonstrate that they are listening to patients but without a paternalistic approach. Conclusion: Staff exhibited most shared decision-making competencies at a good level. However, patients highlighted problems with information sharing and felt staff might not be listening to them. Research and practice should explore tools to address these shortfalls.